2017
DOI: 10.1016/j.ijpharm.2017.06.085
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of tablets using inkjet with UV photoinitiation

Abstract: 2 Additive manufacturing (AM) offers significant potential benefits in the field of drug delivery and pharmaceutical/medical device manufacture. Of AM processes, 3D inkjet printing enables precise deposition of a formulation, whilst offering the potential for significant scale up or scale out as a manufacturing platform. This work hypothesizes that suitable solvent based ink formulations can be developed that allow the production of solid dosage forms that meet the standards required for pharmaceutical tablets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(93 citation statements)
references
References 45 publications
1
92
0
Order By: Relevance
“…In this regard, crosslinking can be induced through theaddition of biocompatible photoinitiators in the presence of UV or visible light source [38]. PEGDA hydrogels can be synthesized rapidly and easily, and their mechanical properties can be readily tuned by varying the concentration or molecular weight (MW) of thepolymer [39].…”
Section: Synthesis Properties and Recent Biomedical Applications Of Phmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, crosslinking can be induced through theaddition of biocompatible photoinitiators in the presence of UV or visible light source [38]. PEGDA hydrogels can be synthesized rapidly and easily, and their mechanical properties can be readily tuned by varying the concentration or molecular weight (MW) of thepolymer [39].…”
Section: Synthesis Properties and Recent Biomedical Applications Of Phmentioning
confidence: 99%
“…To synthesize PEGDA-based hydrogel, the PEGDA powder is dissolved in deionized water at a predetermined mass proportion (e.g.,0.25g PEGDA/ml deionized water) [38]. Photoinitiator Irgacure 2959 is usually added to the PEGDA solution at 0.1 (w/v) and is subsequently exposed to UV light for a few minutes (e.g.,1020min) to complete photopolymerization.…”
Section: Synthesis Properties and Recent Biomedical Applications Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Additive manufacturing is rapidly expanding and modifying the way in which products are designed and manufactured. This technology allows to create complex geometries with customizable material properties, with design freedom and environmental advantage, by transforming designed files into fully functional products. On the other hand, the rapid spread of a wide variety of technologies associated with AM, leads to an absence of a comprehensive set of materials, design principles and manufacturing guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fina et al reported the manufacture 3D printed tablets (Printlets ™ ) with different drug release properties, while Wang et al and Goyanes et al evaluated SLS to manufacture oral dosage forms containing either paracetamol or 4‐ASA and antiacne facial masks for topical drug delivery, respectively. Furthermore, EA Clark et al produced tablets consisting of a cross‐linked PEGDA hydrogel matrix containing the drug and photoinitiated in a low oxygen environment by using an aqueous solution of Irgacure 2959. Furthermore, the versatility of 3DP technologies in the development of drug delivery systems includes gastro‐floating tablets in gastro‐retentive drug delivery systems, personalized oral medicine, medical devices, and wound dressings …”
Section: Polymersmentioning
confidence: 99%